Development of UWB-IR based low power asset tracking system with precise location information - Gupta, Ankur (2018)
Global Positioning System (GPS) and Global Navigation Satellite System (GNSS) are currently widely used for measurement of real time location of assets in tracking applications. However, in densely cluttered indoor environments, direct line of sight signal from satellite is weak and the received signal is dominated by reflected signals (multi-path signals). This causes the receiver to track the multi-path signals resulting in degraded position information or the signal may be so heavily attenuated that it goes below noise floor of the receiver and makes it difficult for the receiver to detect the signal. There is also strong demand for indoor positioning applications driving the need for indoor localization. The goal for this thesis is to develop a low power asset tracking system for the indoor applications. This thesis is commenced with design of energy efficient tags that will be carried by people or objects to be tracked in the indoor environment. The design of tags includes the hardware and firmware development with the aim of achieving energy efficiency as tags are powered by coin size battery. The tags transmit Ultra-Wideband (UWB) signals for the purpose of localization and are commanded through a sub-1 GHz wireless data link. The tags designed to be used in this system are UWB transmitters only. This is done to achieve the low power design parameter for the system as UWB receivers are likely to consume higher power and tags are powered by a coin size battery leading to less operational hours. For the purpose of command and control along with consideration of the low power design parameter, an ultra-low power sub-1 GHz wireless data link is used in comparison to 2.4 GHz band, which is used in many applications resulting into difficulty of achieving the reliable data link. The firmware code is developed for tags to perform sub-1 GHz wireless communication. The three design strategies are presented and implemented in design of tags which aid in achieving the extended battery life. The current measurement results are presented along with computation of battery life. Using battery capacity as 240 mAh in conjunction with the implementation of three design strategies in tag, the battery life of 86 days is achieved at the update rate of 1 Hz with sub-1 GHz Tx power of +10 dBm and UWB Tx power of +23 dBm. The development of indoor localization system is accomplished with design of reader/sensor nodes which includes the hardware and firmware code development. The reader nodes are distributed in indoor environment to receive the UWB signals for the purpose of localization. The localization technique used in the system is based on time difference of arrival (TDOA). The sub-1 GHz wireless data link is used by the reader nodes for intent of command and control. The firmware code is developed for the reader nodes to achieve control over the whole process of indoor localization using the sub-1 GHz wireless data link. The reader cape hardware is designed to be mounted over BeagleBoneBlack (BBB) board. Using low cost ADC, the equivalent time sampling is performed in the reader nodes to sample the UWB signals transmitted by tags. The sampled UWB signals are processed in the BBB board to find time of arrival (TOA) information. The TOA data from all readers nodes is transmitted to the central server where TDOA is computed and localization is performed using difference of TDOA’s. In this system, the energy efficient Medium Access Control (MAC) scheme is designed and implemented for multiple tags indoor localization environment. This scheme is based on centralized architecture controlled by master reader node. The master reader node provides feedback to tags using the sub-1 GHz beacon about allocated time slots. This feedback about the allocated time slots prevents the charge consumed in case of re-transmissions of acknowledgement packets, resulting from collisions due to simultaneous transmission by the tags. The time synchronization is performed between the master reader node and the tags in order to maintain the start time for listening of beacon in the tags in every cycle. This synchronization removes the ideal listening time in the tags. Also, using an ultra low power MCU (CC1310), the charge consumption during the listening of the master reader beacon in the tags is minimized. With this implementation of MAC scheme in the system, the charge consumed in the tags during one cycle is found to be 40 uC. In last, to perform 1D range measurement between reader nodes, the range equation is derived using TDOA in consideration with the clock skew and the clock offset at each of the devices. The experimental set up is developed including 2 reader nodes and 2 reference tags (co-located at readers) for performing 1D range measurement along with the implementation of MAC scheme. The measurement results are presented for different distances between the two reader nodes and from the measurement results, the accuracy is found to be less than 20 cm.